PROBLEMATIKA DISKRESI DALAM SISTEM HUKUM INDONESIA (STUDI TERHADAP UNDANG-UNDANG NO. 30 TAHON 2014) - Heryansyah, Despan (Jurnal Yuridis, 2015)
The existence of discretion on the one hand it is beneficial for administration officials to overcome  the stagnation of government.  Discretion allow a government  official to issue a policy even though there is no legislation that became law umbrella issuance of the policy. But on the other hand, if the discretion is not used in accordance with the procedures and requirements specified will open up opportunities for abuse of power by government officials, which of course would be  detrimental  to the  citizens  as victims. The problem in this research are, first, what is the fruit simalakama discretion to governance? Secondly, how the problems of discretion in the application of laws and regulations in Indonesia after Law No. 30 Year 2014 on Government  Administration? This research is the use of doctrinal primary law and secondary law.  The method  used the normative approach. The study concluded that, tops, discretion has been the fruit othe  governance  dilemma  because  on  the  one  hand  can  overcome  the  stagnation of government but on the other hand open the possibility of abuse of authority. Secondly, there are many problems arising after the enactment of Law No. 30 Year 2014 on Government Administration in particular  with regard to discretion